Risk of dementia in survivors of active tuberculosis in Korea: A nationwide cohort study - Yohwan Yeo; Jung Eun Yoo; Kyungdo Han; Jin-Hyung Jung; Hayoung Choi; Jongkyu Park; Dong Wook Shin; Hyun Lee (Elsevier, 2024)
Background: Concern has been growing regarding post-tuberculosis (TB) morbidities, including neurologic and vascular comorbidities. However, the association between post-TB status and the risk of dementia has been evaluated in only few studies. Therefore, in the present study, the risk of dementia was investigated in a nationwide population-based cohort. Methods: Using the Korean National Health Insurance Service (KNHIS) database, this study included TB survivors (n = 50,182) and matched controls (n = 50,182) for age, sex, and year of index date. The risk of dementia was estimated using Cox proportional hazards regression, and stratified analyses for related factors were performed. Results: During a mean 3.5 years of follow-up, the incidence of dementia was 9.32 for Alzheimer disease and 1.17 for vascular dementia per 1000 person-years for TB survivors and 7.21 and 0.67, respectively, for matched controls. The overall risk of Alzheimer disease was 1.11 (95% confidence interval (CI) 1.03-1.20)-fold higher in TB survivors than in matched controls. For vascular dementia, 1.48 (95% CI 1.16-1.89)-fold higher risk was found in TB survivors than in matched controls. The strength of the association between TB and dementia was higher in CNS TB (aHR 1.76, 95% CI 1.18 -2.64) than non-CNS TB (aHR 1.11, 95% CI 1.05-1.19) compared to controls, especially for patients with vascular dementia (3.33, 95% CI 1.06-10.49). Conclusion: TB survivors had a significantly higher risk of dementia than the general population.